Isolation and purification of proteolytic enzyme produced by lactic acid bacteria from budu and bambangan - Thung, Tze Young (2012)
Proteolytic enzymes have wide applications in various industries. Microorganisms represent an excellent source of proteolytic enzymes owing to their broad biochemical diversity, rapid growth, and low cost for their cultivation. However, the information of extracellular protease of Lactic Acid Bacteria (LAB) is limited. Therefore, an attempt was conducted to study the extracellular protease produced by LAB isolated from local fermented foods, Budu and Bambangan. The extracellular protease activity was determined by qualitative assay using skim milk agar plate and quantitative assay by spectrophotometric method. Out of 41 LAB isolates, 21 LAB exhibited extracellular protease activity over a broad pH range by quantitative spectrophotometric assay. Isolate B12m9 was the highest extracellular protease producer under acidic condition and hence it was selected for further study. The isolate B12m9 was identified as Pediococcus pentosaceus B12m9 by phenotypic and genotypic analyses. Nucleotide sequence of 16S rDNA showed 97% homology to P. pentosaceus. Thus, this isolate was designated as P. pentosaceus B12m9 and its proteolytic enzyme was designated as extracellular protease B12m9. The experiments of cultivation conditions such as initial pH, temperature and incubation time showed that maximum protease production by P. pentosaceus B12m9 occurred at pH 7.0 and 30°C over 20 h of incubation time. The extracellular protease B12m9 was further purified by using Fast Protein Liquid Chromatograph. Four protease isozymes were produced by P. pentosaceus B12m9 as different protease activity of the ammonium precipitated proteases were detected. Peak G extracellular protease was purified to apparent homogeneity by ammonium sulphate precipitation, Resource Q anion-exchange chromatography and Superose-12 gel filtration chromatography with a recovery yield of 19% and purification fold of 62.53. The molecular mass of the purified protease was estimated to be 14.4 and 14.5 kDa by Glycine sodium dodecyl sulphate – polyacrylamide gel electrophoresis and Superose-12 gel filtration chromatography, respectively. The isoelectric point of the purified protease as revealed by isoelectric focusing electrophoresis was approximately 8.0. In conclusion, different LAB produced different types of extracellular protease and the purified extracellular protease B12m9 was an alkaline protease, where the potential of the purified extracellular protease has to be explored further.